PENILAIAN KINERJA SISTEM IRIGASI MENGGUNAKAN INDIKATOR UNTUK PEMBUATAN KEPUTUSAN - Rizal Syahyadi; Ibrahim Ibrahim (Politeknik Negeri Lhokseumawe, 2013)
This study involves the assessment of the performance of technical irrigation system in Aceh, Indonesia, namely the Pante Lhong technical irrigation system. The Pante Lhong technical irrigation system performances were evaluated using measured internal and external indicators that covered different aspect of evaluation. The Rapid Appraisal Process (RAP) is a visual assessment tool was used to evaluate the internal indicators performance. The selected indicators were grouped in terms of actual water delivery service performance and infrastructure maintenance. The external indicators were crop yield and production cost. The data are collected from the farmers in the three regions which were upstream, middle stream and downstream. Data were collected through field observation and face to face interviews with the irrigation staff and the farmers. The results for the infrastructure maintenance indicators showed that the current canal network received 74.25 % of the expected infrastructure maintenance. The results also found that the continuous supply method is quite enough to excellent performance of flexibility, reliability and equity of water distribution. However, the control flow to farmers in the next level at third canal/tertiary level and measurement of volumes delivered sub components had performed at worse than expected. In the crop yield indicator, the average maximum productivity was 3.91 ton/ha and the income generated was Rp. 11.730 million rupiahs/ha. The total production cost of the Pante Lhong technical irrigation system was Rp. 4.126 million rupiahs/ha and hence in term of return of investment (ROI), it is still profitable and feasible to be developed for the farmers.